UNISON framework of model-based innovation for collaborative innovation of smart product-service system design. (September 2022) - Zhang, Ke; Feng, Lijie; Lin, Kuo-Yi; Wang, Jinfeng; Liu, Kehui; Zhang, Luyao
Highlights: A systematic smart PSS design approach is proposed on the UNISON framework. Factors of multi-stakeholder collaborative innovation are explored by text mining. Morphology analysis model is introduced to smart PSS alternative generation. Smart PSS design alternatives are ranked by the group TFN-based fuzzy TOPSIS. The framework is validated by smart drainage equipment-service system design. Abstract: With the emerging trend of digital servitization, manufacturers have transformed toward developing and providing smart product-service system (smart PSS) which is considered with great potential. As a value co-creation strategy, the innovative design of smart PSS involves multiple stakeholders, and the decisions in the concept design stage are especially crucial for its success throughout the whole lifespan. However, recent studies have focused on developing the design methodology or decision approaches for it, with an absence of the systematic decision framework for smart PSS innovation design. Most of them held the customer-centric viewpoint without considering the aspect of multi-stakeholder collaborative innovation. To fill the gaps, this study proposes the UNISON framework of model-based innovation for smart PSS design from the perspective of collaborative innovation, to assist its innovative design and decision-making in the concept design stage. To illustrate the structured procedures and demonstrate the validity of this framework, it was applied in an empirical study for the innovative design of smart drainage equipment-service system. Moreover, the performance of the proposed framework has been discussed from both theoretical and practical aspects. This study can provide systematic guidance for developing smart PSS innovative design strategies to facilitate multi-stakeholder collaborative innovation.